2016
DOI: 10.1007/s13277-016-4983-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher EZH2 expression is associated with extramedullary infiltration in acute myeloid leukemia

Abstract: Accumulating evidence indicates that enhancer of zeste homolog 2 (EZH2) promotes the metastatic ability of solid tumors, but the role of EZH2 in extramedullary infiltration (EMI) in acute myeloid leukemia (AML) has not been thoroughly explored. In the present study, we investigated the possible association between EZH2 and EMI. We found that the messenger RNA (mRNA) and protein expression levels of EZH2 in AML patients were both significantly higher than in idiopathic thrombocytopenic purpura (ITP) patients. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…However, the expression pattern of EZH2 remains controversial in AML. 17 In contrast, Göllner et al demonstrated that loss of the histone methyltransferase EZH2 17 In addition, EZH2 silencing resulted in decreased proliferation and migration ability and increased apoptosis, suggesting its oncogenic role in AML.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the expression pattern of EZH2 remains controversial in AML. 17 In contrast, Göllner et al demonstrated that loss of the histone methyltransferase EZH2 17 In addition, EZH2 silencing resulted in decreased proliferation and migration ability and increased apoptosis, suggesting its oncogenic role in AML.…”
Section: Discussionmentioning
confidence: 99%
“…17 In addition, EZH2 silencing resulted in decreased proliferation and migration ability and increased apoptosis, suggesting its oncogenic role in AML. 17 In contrast, Göllner et al demonstrated that loss of the histone methyltransferase EZH2…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The roles of PcG genes in LAML are elusive. High expression of EZH2 gene, coding PRC2 catalytic subunit, is associated with extramedullary infiltration in LAML and EZH2 silencing suppresses cell proliferation, cell migration and increases cell apoptosis in LAML through inhibiting MMP2 expression and increasing E-cadherin expression (Zhu et al 2016). However, lower EZH2 expression also correlates with poorer prognosis of LAML patients due to loss of EZH2 inhibits the expression of HOX gene and results in enhancing chemo-resistance of LAML cell lines (Gollner et al 2017).…”
Section: Introductionmentioning
confidence: 99%